American Journalism and the Landscape of Secrecy: Tad Szulc, the CIA and Cuba. Issue 340 (27th March 2015) - Aldrich, Richard J.
Abstract: The relationship between secret services and the press is an enduring one. Although the CIA did not seek the kind of salient media profile enjoyed by the FBI, it nevertheless maintained an informal press office from its foundation in 1947. Directors of the CIA and their senior staff devoted significant time to the public profile of the Agency. Their efforts to engage with the world of newspapers divided journalists. Some saw it as their patriotic duty to assist the Agency, even reporting for it overseas, while other saw it as their constitutional role to oppose the Agency. This was especially true during the Vietnam War and Watergate. Thereafter, a more nuanced relationship developed in which the press saw themselves as an informal wing of new accountability processes that provided the intelligence community with oversight. This was ambiguous terrain and its complexities are explored here by focusing on the example of the prominent New York Times journalist Tad Szulc, whose complex relationship with the CIA spanned several decades and connected closely with the vexed issue of Kennedy and Cuba. Szulc played a number of roles including outrider, renegade and overseer, but there was confusion about who was servant and who was master.